1 Public Records of the Colony of Connecticut 113-14 (J. Hammond Trumbull ed., 1850) (enacted 1644) - (:unkn) unknown (My University, 1644)
§ 130: Prohibited selling or trading "to the Indeans," nor any Dutch or Frenchman any guns, pistols, and other warlike instruments. Violators fined "twenty for one" and corporal punishment at the court's discretion.
Keywords: TRANSFER - DANGEROUS PERSONS